GENERAL RULES OF INTERROGATION, INVESTIGATIVE ACTION: RESULTS AND TRENDS - Абдураззақов Содиқжон Хусан ўғли (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses in detail the basic rules and procedure for conducting an investigative action - interrogation, the procedure for processing the results of this investigative action and its significance in the investigation of criminal cases. The tactics of interrogation and its types were analyzed depending on the condition of the interrogated. The main methods of obtaining evidence through interrogation by interrogators and investigators in criminal cases are analyzed. The opinions of leading scientists and law enforcement practice are analyzed.